Circular economy in firms’ strategies: What are the determinants of eco-innovation? - Massapina, M.; Meireles, M.; Madaleno, M. (Environment, Development and Sustainability, 2025)
Sustainability is a growing theme in society, and associated with it is the concept of circular economy (CE) that tries to reuse products for greater durability, thus contributing to reducing waste and pollution. A very important agent in this topic is eco-innovation (EI), which can be developed to promote the growth of this new economic concept. This study intends to determine the key drivers of EI for Portuguese companies, considering their evolution towards a circular economy. Using a Tobit model and data from the CIS, all the variables identified in the literature review were tested to understand their impact on firms’ performance by measuring turnover growth (TG). Verifying all variables’ effects was impossible from the estimations because not all were significant. Our findings allow concluding that not all drivers that appeared to have a positive impact on the TG had one. Therefore, the results show that not all theoretical drivers of eco-innovation are, in fact, drivers and may even represent negative impacts for the company, contrary to what one would predict. The negative effect that is still notorious regarding the costs that companies have associated with the implementation of these new measures should also be highlighted. It represents one of the biggest inhibitors for companies to integrate this action into their internal strategies.